Peculiarities of Life Expectancy Across the Regions of countries (Kazakhstan) - Larissa Bazarbayeva; Amina Sarsenbay; Makhabbat Khaval; Meyirzhan Yerzhanov (European Research Materials, 2026)
The current research analyzes factors influencing life expectancy among various regions of Kazakhstan by applying official statistics and correlation methods. According to the results obtained, the strongest correlations are found for such factors as the size of catering market, spending on R&D activities, and the number of institutions providing higher education. Moreover, significant correlations are identified between life expectancy and employment rate, population, and marriage rate. Using these findings, regions of Kazakhstan will be divided into several groups for comparison purposes in order to find out how important factors influence longevity differently in various regions